1995
DOI: 10.2307/2291167
|View full text |Cite
|
Sign up to set email alerts
|

Permutation Tests: A Practical Guide to Resampling Methods for Testing Hypotheses.

Abstract: Building a minimal spanning tree. Library of Congress Cataloging-in-Publication Data Good, Phillip I. Permutation tests: a practical guide to resampling inethods for testing hypothesesjPhillip Good. p. cm.-(Springer series in statistics) Inc1udes bibliographical references and index. 1. Statistical hypothesis testing. 2. Resampling (Statistics) I. Title. 11. Series.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 0 publications
0
43
0
2
Order By: Relevance
“…Additionally, canonical variate analyses (CVA) were performed to maximize the differentiation in anchor shape between groups. Procrustes distances between groups were calculated using a permutation test (Good 2001) with 10,000 randomizations ( = 0.05). The main axes of the PCA and CVA were visualized using wireframe diagrams (Klingenberg 2011).…”
Section: Geomorphometric Analyses and Size Of The Anchorsmentioning
confidence: 99%
“…Additionally, canonical variate analyses (CVA) were performed to maximize the differentiation in anchor shape between groups. Procrustes distances between groups were calculated using a permutation test (Good 2001) with 10,000 randomizations ( = 0.05). The main axes of the PCA and CVA were visualized using wireframe diagrams (Klingenberg 2011).…”
Section: Geomorphometric Analyses and Size Of The Anchorsmentioning
confidence: 99%
“…Although there seems to be a horizontal shift in the estimated x-axis intercepts in different experiments, these intercept values were similar across experiments (2.19 vs. 2.28). We tested whether these mean estimates were statistically different from one another by fitting these iso-effort patterns based on data with shuffled experiment labels, which created an empirical null distribution with minimal statistical assumptions (Good, 2013). Across 10,000 iterations, we found that the observed x-axis intercept difference between experiments was not statistically different from the null values (bootstrapped p = .65).…”
Section: Equating Physical and Cognitive Effortsmentioning
confidence: 97%
“…1. A permutation test (also called randomization test) 45,46 for the co-expression that was used to build the dendrogram. We wanted to determine the statistical significance of the frequencies in the first column of Table 1, which contains the Mus musculus data analyzed with DCS, and we therefore used a control where the ordering of the dendrogram was no longer dependent on the correlation of the receptors' gene expression.…”
Section: Statistical Analysis Of Comberonsmentioning
confidence: 99%